Animations to illustrate the Autocalibration process of accelerometer data - van Hees, Vincent (Apollo - University of Cambridge Repository, 2014)
Supplementary graphics for paper "Autocalibration of accelerometer data collected in daily life based on local gravity and temperature: an evaluation on four continents"
.avi files: animation_a_6_3D_prepostautocal.avi – 3D animation showing static points before and after autocalibration process. animation_c_4_2D_duringautocal.avi – 2D animation showing how static points moved during autocalibration. animation_d_3_3D_duringautocal.avi – 3D animation showing how static points moved during autocalibration.